Implementation of Complete Systematic Land Registration Regulation in order to Achieve Legal Certainty in Indonesia - Nadila Maysila Herdarezki; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
This legal research aims to examine the implementation of regulations on the Complete Systematic Land Registration in order to achieve legal certainty in Indonesia. This legal research is a normative or doctrinal legal study conducted with a review of the literature. The research approach is conducted using statue approach and legal comparison approach (comparative law). This legal research uses both primary and secondary legal materials regarding the implementation of the Complete Systematic Land Registration in Indonesia. Based on the results of this legal research, implementation of the Complete Systematic Land Registration Program is a form of policy issued by the Indonesian Government with the Ministry of Agrarian Administration/National Land Agency to register land that has not owned a proprietary certificate. In order to achieve the legal certainty for the community is required improvement of good quality of public awareness, implementation mechanisms and various parties related to the Complete Systematic Land Registration in Indonesia. Keywords: land; complete systematic land registration; legal certainty; policy